1996
DOI: 10.1002/(sici)1096-9071(199606)49:2<132::aid-jmv10>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of RIBA-3 supplementary test to HCV PCR positivity and genotypes for HCV confirmation of blood donors

Abstract: HCV antibody screening of 624,910 blood donations resulted in 3,832 samples being referred for confirmation. All were tested by RIBA-3 with 2,710 negative, 945 indeterminate and 177 positive results. HCV RNA was detected by PCR in an average of 69.5% of RIBA-3 positives (4 bands 84.1%; 3 bands 74.1%; 2 bands 34.1%) and only 0.53% of RIBA-3 indeterminates. Eighty-four percent of samples with a total RIBA-3 band intensity score (maximum 16) of > or = 8 were PCR positive compared with only 22% of those with a sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
37
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 10 publications
7
37
1
Order By: Relevance
“…Different studies performed with these assays have shown that the NS5 antigen is not as immunoreactive as the other antigens (4,15) and is potentially less specific than any of the other HCV antigens included in the third generation of commercially available diagnostic assays (11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Different studies performed with these assays have shown that the NS5 antigen is not as immunoreactive as the other antigens (4,15) and is potentially less specific than any of the other HCV antigens included in the third generation of commercially available diagnostic assays (11).…”
Section: Discussionmentioning
confidence: 99%
“…Regions of nonspecific antigenic reactivity can be found within different HCV proteins, including the NS5 protein (11). One study showed that more than 30% of the 543 synthetic peptides derived from different regions of the HCV polyproteins of different genotypes were recognized by antibodies from healthy blood donors (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because comparing an HCV RNA-based PCR assay with an anti-HCV-based assay is not practical, we cannot directly compare PCR-based results with those obtained using our protein microarray assays. However, the overall accuracy of our protein microarray method is nearly equivalent or better than that of the LIBA-blot based confirmatory test (19 ). The inclusion of additional antigens such as NS4 would improve the specificity of this protein microarray-based assay.…”
mentioning
confidence: 93%